ANALISIS TINGKAT PARTISIPASI PEMILIH PEMULA PASCA KETETAPAN KOMISI PEMILIHAN UNUM TENTANG 10 PARTAI PESERTA PEMILU 2014 DALAM PEMBANGUNAN POLITIK MASYARAKAT - Agung Suprojo (Universitas Tribhuwana Tunggadewi, 2013)
Party democracy in Indonesia was held as a political event in choosing members of the legislature and the executive vice president and president. Post-reform Indonesia has proven that the implementation of direct democracy party , general , free and secret afford held peacefully , but still a bit of observers who analyze the sustainability of future elections - the future . The General Election Commission has set 10 Party General Election 2014 Participant pursuant to the provisions of Law No. 8 Year 2012. The problem of political participation can not be separated from the element of interest voters to obtain information political developments in a wide variety of information media in Indonesia. The attitude at the level of voter apathy can be used as benchmark beginners over the level of success of the 2014 election. Through SWOT analysis, the authors develop the strategic direction of the steps in anticipation of the birth of the attitude of apathy among voters are portrayed as the following description: democratic political apathy on the higher time voters, media information is not favored voters Politics, New voters never get education and political socialization, the National Election Commission must consider the potential voters. , strategic steps to do the General Election Commission should involve various elements of electronic information media providers and media printed information. Voters had the opportunity to get a lesson or political education through the Institute of Education Formal environment.